Simultaneous Displacement/Force Self-Sensing in Piezoelectric Actuators and Applications to Robust Control - Rakotondrabe, Micky; Ivan, Ioan Alexandru; Khadraoui, Sofiane; Lutz, Philippe; Chaillet, Nicolas (IEEE/ASME transactions on mechatronics, 2015)
Self-sensing technique consists of using an actuator as a sensor at the same time. This is possible for most actuators with physically reversible principle such as piezoelectric materials. The main advantages of self-sensing are: 1) the embeddability of the measurement technique, and 2) its low cost as no additional sensor is required. This paper presents a self-sensing technique for piezoelectric actuators used in precise positioning applications like micromanipulation and microassembly. The main novelty is that both displacement and force signals can be simultaneously estimated. This allows a feedback control using one of these two signals with a display of the other signal. To demonstrate this advantage, a robust H ∞ feedback control on displacement with real-time display of the force is used as an application of the proposed self-sensing technique. In this paper, experimental results obtained with a piezoelectric cantilever actuator validate and demonstrate the efficiency of the proposed self-sensing.